Age estimation based on length measurements and otolith analyses of the three-spined stickleback (Gasterosteus aculeatus) from freshwater lakes in south Iceland. - Anna Bára Másdóttir 1994- (2018)
The knowledge acquired from aging fish and discovering their growth rate at both the daily and the yearly scale is not only informative of the biology of the species itself, but also the environment it lives in. Different fish aging techniques are available and the one most commonly used involves counting periodic growth increments of calcified or bony structures, such as otoliths. Otoliths grow constantly over the fish‘s lifespan accumulating seasonal layers of calcium carbonate called annuli and thus are ideal for age analysis. Another aging technique regularly used involves plotting a length-frequency histogram and identifying patterns of modes that correspond to each age group of the fish species. Here both of these methods are used to analyse the annual age of three-spined sticklebacks (Gasterosteus aculeatus) from two different freshwater lakes in Iceland. The number of annuli are counted on the otoliths for each fish, and the relative length of the annuli from the otolith core (annuli radii) is measured. This information is used to predict at what size of the sticklebacks on average the annuli start to form. There is a considerable difference between the lakes at what sizes the annuli are forming which could be explained by different features of the lakes, such as temperature. Length-frequency histograms are made from larger data sets and the mean size of each age group from this study is superimposed on the graphs to compare them to the modes. The average fish lenght of each age group does not correlate to the pattern of modes in the histograms for either of the lakes, so the analysis of the annuli is more appropriate for age estimations of the stickleback than length based approaches. By knowing more precisely the time of breeding and egg hatching of sticklebacks in these two lakes, the analysis of the Icelandic stickleback would have however improved with more accurate results.